Analisis PLTS Sebagai Sumber Daya Sistem Pakan Ikan Otomatis - Muhammad Idris; Indra Hermawan; Iswandi Iswandi; Felix Darwin Jaya Waruwu (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2022)
The purpose of this study was to determine the angle of inclination of the 10 WP solar panel so that the maximum amount of sunlight that falls on the surface area of the solar cell, analyze the performance of the solar cell, calculate the duration of charging the battery using a 10 WP solar panel. The method used is an experiment by recording every 10 minutes the output current and voltage of a 10 WP solar panel and battery, the current and voltage entering the battery and recording the intensity of sunlight using a solar meter. The overall results, based on theory and experiment, are that the angle of inclination of the solar panel is 10 WP so that the maximum amount of sunlight that falls on the surface area of the solar cell is at an angle of 9.3620 at 12.00 WIB facing south where the instantaneous intensity of sunlight hitting the solar panel at is 1049 W/m2, the performance of the solar cell is obtained by an average output current of solar panels 0.1295 A, the average output voltage of solar panels is 14.3162 V, the average output power of solar panels is 1.8798 W, the average the power that hits the solar panel is 59.3811 W, and the average panel efficiency is 3.1707%, the duration of charging the battery using a 10 WP solar panel is approximately 29 hours 8 minutes so that the battery is fully charged or approximately 2 days 5 hours 8 minutes.